VIABILITY OF CRITICALLY ENDANGERED CEBU CINNAMON SEEDS (CINNAMOMUM CEBUENSE L.) - Lillo, Edgardo P.; Alcazar, Steve Michael T. (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 16 No. 1, 2013, 2018)
The study aimed to determine the viability of the seeds of the critically endangered Cebu Cinnamon (Cinnamomum cebuense L.) species. The collected seeds were air- dried and stored in a closed container. The stored seeds were sowed in the seed box at an interval of one week. This study consists of nine (9) treatments with three (3) replications, laid out in a Randomized Complete Block Design and analyzed using ANOVA at 5 percent level of significance. Results show that there is a significant difference among the treatments. For Treatment control (To) the seeds were sown directly to the soil medium after air drying. In this treatment many seeds have germinated. The result implies that Cebu Cinnamon seeds should be sown directly to the soil medium right after air drying rather than storing it in the container. The seeds that have germinated were considered as viable. Cebu cinnamon was very sensitive to temperature changes. The seeds of Cebu Cinnamon species should be collected when they are matured to ensure their viability, thus promote higher rate of germination. Conservation and protection o f the Cebu Cinnamon species must be considered one of the priorities species of the government and other stakeholders because there are much less of the species that are left on the island.